Prolonged nightly fasting in older adults with memory decline: A single-group pilot study exploring changes in cognitive function and cardiometabolic risk factors - Dara L. James; Linda K. Larkey; Molly Maxfield; SeungYong Han; Edward Ofori; Alex E. Mohr; Nanako A. Hawley; Kate Alperin; Erica Ahlich; David E. Vance; Dorothy D. Sears (Journal of Clinical and Translational Science)
Abstract